The Danish Psychosocial Work Environment Questionnaire (DPQ): Development, content, reliability and validity - Clausen, Thomas; Madsen, Ida EH; Christensen, Karl B; Bjorner, Jakob Bue; Poulsen, Otto Melchior; Maltesen, Thomas; Borg, Vilhelm; Rugulies, Reiner (Scandinavian Journal of Work, Environment & Health, 2019)
' ' OBJECTIVES ': 'The aim of this study was to describe the development and the content of the Danish Psychosocial Work Environment Questionnaire (DPQ) and to test its reliability and validity. ' ' METHODS ': 'We describe the identification of dimensions, the development of items, and the qualitative and quantitative tests of the reliability and validity of the DPQ. Reliability and validity of a 150 item version of the DPQ was evaluated in a stratified sample of 8958 employees in 14 job groups of which 4340 responded. Reliability was investigated using internal consistency and test-retest reliability. The factorial validity was investigated using confirmatory factor analysis (CFA). For each multi-item scale, we undertook CFA within each job group and multi-group CFA to investigate factorial invariance across job groups. Finally, using multi-group multi-factor CFA, we investigated whether scales were empirically distinct. ' ' RESULTS ': 'Internal consistency reliabilities and test-retest reliabilities were satisfactory. Factorial validity of the multi-item scales was satisfactory within each of the 14 job groups. Factorial invariance was demonstrated for 10 of the 28 multi-item scales. The hypothesis that the scales of the DPQ were empirically distinct was supported. The final DPQ version consisted of 119 items covering 38 different psychosocial work environment dimensions. ' ' CONCLUSIONS ': 'Overall, the DPQ is a reliable and valid instrument for assessing psychosocial working conditions in a variety of job groups. The results indicate, however, that questions about psychosocial working conditions may be understood differently across job groups, which may have implications for the comparability of questionnaire-based measures of psychosocial working conditions across job groups.
Keywords: Danish Psychosocial Work Environment Questionnaire; Denmark; job characteristic; occupational health; psychosocial work environment; psychosocial working environment; reliability; stress; survey; validity; work characteristic; working condition